Challenges in Pediatric Cardiac Anesthesia in Developing Countries - Cvetkovic, Mirjana (Frontiers in Pediatrics, 2018)
Introduction: Approximately 90% of a million children worldwide born with congenital heart defect do not have an access to adequate pediatric cardiac care. The World Society for Pediatric and Congenital Heart Surgery, established in 2006 shifted the focus from providing individual pediatric cardiac care to developing global standards for the practice of pediatric cardiac surgery and professional education of the local teams. Materials and Methods: After recognizing the challenges of the local team regarding providing safe anesthesia and functioning as a broader team, we have focused our education on simplifying anesthetic procedures and advancing structured team approach. The appropriate selection of patients and simplifying anesthetic technique should be the standard of care. We introduced structured approach to daily education using just in time teaching, case based discussions and simple skill training simulation sessions. Furthermore, we enhanced team-training approach applying tools such as WHO surgical safety checklist and implementation manual, SAFE communication, introducing KDD with SMART aim, SCAMPs, advanced protocols of care and culture change tools. Results: Following a significant number of short missions to developing centers we have, within NGO, succeeded to support building and maintaining several local pediatric cardiac centers with structured approach to anesthesia and team building. Conclusion: The appropriate selection of patients is one of the most important contributing factors for decreasing morbidity and mortality rate in pediatric cardiac surgery patients. The anesthesia technique for pediatric cardiac procedures should be aimed at fast-track surgery, with early extubation as a goal. Regional blocks such as paravertebral and caudal should be considered for perioperative pain control. By introducing structured approach to daily education and by enhancing team-training approach we have contributed evolving sustainable pediatric cardiac centers in developing countries.